Analisis Komparasi Efisiensi Pengelolaan Persediaan Plat Stainless steel 3mm Pada Produk Mesin Peras Santan Otomatis dengan Metode Just in Time dan Economic Order Quanitity (Studi Kasus PT. Cahaya Agro Teknik-Kota Surabaya) - Gatot Basuki H.M; Ali Ali Sulton (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2026)
This study aims to analyze and compare the efficiency of inventory management for 3mm stainless steel plates used in the production of automatic coconut milk extractor machines at PT. Cahaya Agro Teknik. The company currently implements a routine ordering policy without an optimized quantitative approach, resulting in high inventory costs. Based on the analysis, the Economic Order Quantity (EOQ) method can reduce total inventory costs from IDR 4,444,000 to IDR 2,667,200 by recommending an optimal order quantity of 20.5 sheets with two orders per year. Meanwhile, the Just in Time (JIT) method demonstrates greater cost efficiency, with potential savings of over IDR 3 million depending on the ordering scenario. The comparison reveals that the JIT method is more effective in minimizing inventory costs and improving overall inventory efficiency. Therefore, JIT is recommended as the most suitable approach to support the raw material needs of the company's production process.